On conditions for dynamic stability in discrete specifications of a monetary model - Peel, DA (Economic & Social Studies, 1980)
The purpose of this paper is to examine the stability conditions obtained in some discrete specifications of a continuous time macroeconomic model in which the rate of inflation and the level of output are linked via an augmented Phillips curve and price expectations are formed adaptively. It is shown that if excess demand has a lagged influence on inflation in the Phillips curve, then dynamic instability is a strong empirical possibility. The implications of this result are commented upon.
Keywords: Economics; Sociology